PERWATAKAN TOKOH UTAMA DALAM KUMPULAN CERITA “SETENGAH PECAH SETENGAH UTUH”KARYA PARLINDUNGAN MARPAUNG - Magdalena M. Manao (Universitas Nias Raya, 2021)
The uniqueness of the characterization system in the collection of stories from ParlindunganMarpaung's Half-Pecah Half-Utuh is the background of this research. This study aims to describe the character of the main character analytically and dramatically in the collection of short stories Half Pecah Half Utuh by Parlindungan Marpaung. Disposition is the description of a character or character that tells the events or events of the story picture. The method used in this research is a descriptive qualitative approach. The source of data in this study is data from documents. Data collection technique in this research is documentation technique. The data analysis technique used in this study is the data analysis technique of the Miles and Huberman model by carrying out the steps, namely Data Reduction (Data Reduction), Data Display (Data Presentation) and verification (drawing conclusions). The results of the study show that there are four main character traits analytically, namely loyal, great in leading, brave, and firm and fair. There are seven main character traits that are dramatic, namely committed, caring/understanding, loyal and obedient, intelligent, brave, firm, and willing to sacrifice. To students of the Indonesian language and literature education study program to continue to improve their ability to appreciate short stories as a part of developing literary works. To teachers/educators, to continue to contribute understanding and thoughts for the development of literary science, To readers, to continue to learn to increase knowledge and insight about literature and to share knowledge with the wider community, To other researchers to conduct further research.